If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying w = 2(n + 20) + 0.3(n + 20) Reorder the terms: w = 2(20 + n) + 0.3(n + 20) w = (20 * 2 + n * 2) + 0.3(n + 20) w = (40 + 2n) + 0.3(n + 20) Reorder the terms: w = 40 + 2n + 0.3(20 + n) w = 40 + 2n + (20 * 0.3 + n * 0.3) w = 40 + 2n + (6 + 0.3n) Reorder the terms: w = 40 + 6 + 2n + 0.3n Combine like terms: 40 + 6 = 46 w = 46 + 2n + 0.3n Combine like terms: 2n + 0.3n = 2.3n w = 46 + 2.3n Solving w = 46 + 2.3n Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Simplifying w = 46 + 2.3n
| x^2+y^2-6y+4=0 | | 2(4x-3)-3x=-4 | | .5(6-2x)=-9x-.5(-4x+6) | | 3T^4-48T^4=0 | | -21-9n+2n=10n-20 | | 7x+8=7x-2 | | 0.5(4z+6)+1.4=0.6(4z-6) | | 6n+x=42 | | V+1.5=5.18 | | 6(x+9)=36x | | 2(32)+2(x)=576 | | 1-1.2x=5 | | 8+3(5x-6)=5-5(2x+1) | | 3x=-2x+3-2 | | 7+4(4x-4)=7-4(2x+2) | | 7n=688 | | -4+9(2)=5(2) | | -4+9(1)=5(1) | | -4+9y=5y | | 3log(x)-6=0 | | m-80=1505x | | 8x+11y=211000 | | (w^2-6w)(w^2-6w)=0 | | 14x+72=95 | | 7(x+8)+4=10x-3(x-6) | | -12(x-11)=-9(1+7x) | | 7m-23=2m+2 | | 3x^2+675=27 | | (7+u)(3u-5)=0 | | 3x-26=x+82 | | 3+4.5=8.9 | | 5=x-(-17) |